Pendidikan Islam Usia Dini, Remaja, dan Dewasa Analisis Hadis Laisa Minna dari Kisah Nabi Yusuf AS - Khasanah, Amalia Uswatun; Rohman, Khusni Nur (IIQ An Nur Yogyakarta, 2025)
Islamic education is a lifelong process encompassing all stages of human development, from early childhood and adolescence to adulthood. This paper aims to analyze the concept of cross-age education in Islam by interpreting the meaning of the hadith “Laisa Minna man lam yarham shaghirana wa yuwaqqir kabirana” and the educational values contained in the story of Prophet Yusuf (AS). The study employs a qualitative approach based on literature review with descriptive analysis. The findings indicate that Islamic education emphasizes compassion towards children, character building and self-control in adolescents, and social and spiritual responsibility in adulthood. The main challenges in implementing age-based Islamic education in the modern era include the influences of digitalization and globalization, as well as limited awareness among parents and teachers regarding developmental psychology approaches. This paper recommends collaborative efforts among families, schools, and communities to develop a contextualized, humanistic, and relevant model of Islamic education that addresses the developmental needs of learners today.